Issues and problems relating to the passage of the appropriation bill in Nigeria / Adebayo T. Salami - T. Salami, Adebayo (Universiti Teknologi MARA, 2022)
Nigeria's 1999 Constitution (as amended) is unique in many important respects. Among others, it was conceived and expressly written by the military. This no doubt raises quite significant epistemological issues and problems of concern in political and legal theories. The constitution clearly indicates that the responsibility of the legislature is primarily law-making and therefore has contained in it clear provisions and references. There are however, quite polemical issues and problems arising from the passage of the yearly Appropriation Bill into law. The paper concerns itself with these polemical issues and problems. Consequently, what are these issues and problems? Why are, or what and what make the issues and problems polemical? How can these issues and problems be resolved? And what relationships in theory and practice, that can be formulated between the resolution of these issues and problems and democratic political stability in Nigeria? The approach of the paper includes a critical examination and analysis of the contentious arguments and debates in legal and political theories with respect to the role of the military in constitution drafting in transitional societies. It further includes the discussion and evaluation of the aspects of the constitution relating to the control of public funds. Finally, it provides recommendations on the reform of the administrative and political processes and procedures relating to the exercise of power and control of public funds and monies within the framework of the constitution as a way of reducing and eliminating the contentions between and among the organs of government especially between the executive and legislature.